2021
DOI: 10.3389/fpsyg.2021.708808
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Mindfulness, Depression, Anxiety, and Quality of Life in Individuals With Schizophrenia Spectrum Disorders

Abstract: Background: Schizophrenia spectrum disorders (SSD) are frequently accompanied by comorbid depressive and anxiety symptoms, as well as impaired quality of life (QoL). A growing body of evidence has demonstrated the relevance of mindfulness for SSD in recent years. The study examined the association between mindfulness, depression, anxiety, and QoL.Materials and Methods: A total of 83 participants with SSD were recruited at the in- and outpatient psychiatric hospital care. Participants completed the Southampton … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…50 A recent mediation analysis also suggested that negative emotion might mediate the relationship between DM and clinical outcomes, such as quality of life, in people with SSDs. 51 These results showed that increased DM was associated with improved emotions and psychotic symptoms in people with SSDs. Rumination is highly associated with negative emotions and psychotic symptoms and has been supported as a buffer between DM and psychiatric symptoms in clinical populations and SSDs.…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…50 A recent mediation analysis also suggested that negative emotion might mediate the relationship between DM and clinical outcomes, such as quality of life, in people with SSDs. 51 These results showed that increased DM was associated with improved emotions and psychotic symptoms in people with SSDs. Rumination is highly associated with negative emotions and psychotic symptoms and has been supported as a buffer between DM and psychiatric symptoms in clinical populations and SSDs.…”
Section: Introductionmentioning
confidence: 84%
“…The findings were consistent with previous studies and a recent mediation analysis that found acting with awareness and nonjudging to be significant predictors of depression and anxiety, while describing and observing were found to be unable to predict depression and anxiety in the general population and people with SSDs. 51,76,77 Acting with awareness and nonjudging were suggested to have a substantial role in the prediction of rumination and mental health outcomes, particularly depressive symptoms and quality of life. 51,76,77 Individuals who were judgemental and lacked awareness were found to have higher levels of depression and anxiety and were more inclined to self-criticise and ruminate on negative feelings rather than responding with awareness and self-acceptance, potentially exacerbating and maintaining psychopathological symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations